SPORTS FOR ALL: POLITICS, STRATEGIES, CONCEPTIONS - CONSEQUENCES FOR PHYSICAL EDUCATION AND PUBLIC SPORTS (Fiep Bulletin - online, 2012)
Starting at some definitions, the author presents different views on sport which, however, share the sameprinciple: sport as a competitive practice. The author points out the changes, such as the growing conscience of thebody and the appearance of a set of new sports that have generated a new "Sports Culture" and made "Sport for All"more than simple competition. The paper shows that people practice sports for different reasons, but the vastmajority of non-top-athlete do it for the "health – fitness – fun" complex of motivations; and this impacts on whattype and how “Sports for all” is offered. The way the public system deals with sports and how the public budget isused is also commented. The consequences of these changes for Physical Education and public sport organisationsare discussed together with some suggestions for their improvement. The idea is to build the “sports culture” duringschool years so that students will keep on practicing sports later. The paper ends by presenting some examples ofsuccessful “Sport for All” experiences around the world.
Keywords: physical education; sports culture; sport for all; conceptions